Analysis of metal(loid)s contamination and their continuous input in soils around a zinc smelter: Development of methodology and a case study in South Korea. (July 2018) - Yun, Sung-Wook; Baveye, Philippe C.; Kim, Dong-Hyeon; Kang, Dong-Hyeon; Lee, Si-Young; Kong, Min-Jae; Park, Chan-Gi; Kim, Hae-Do; Son, Jinkwan; Yu, Chan
Abstract: Soil contamination due to atmospheric deposition of metals originating from smelters is a global environmental problem. A common problem associated with this contamination is the discrimination between anthropic and natural contributions to soil metal concentrations: In this context, we investigated the characteristics of soil contamination in the surrounding area of a world class smelter. We attempted to combine several approaches in order to identify sources of metals in soils and to examine contamination characteristics, such as pollution level, range, and spatial distribution. Soil samples were collected at 100 sites during a field survey and total concentrations of As, Cd, Cr, Cu, Fe, Hg, Ni, Pb, and Zn were analyzed. We conducted a multivariate statistical analysis, and also examined the spatial distribution by 1) identifying the horizontal variation of metals according to particular wind directions and distance from the smelter and 2) drawing a distribution map by means of a GIS tool. As, Cd, Cu, Hg, Pb, and Zn in the soil were found to originate from smelter emissions, and As also originated from other sources such as abandoned mines and waste landfill. Among anthropogenic metals, the horizontal distribution of Cd, Hg, Pb, and Zn according to the downwind direction and distance from the smelter showed a typical feature of atmospheric deposition (regression model: y  =  y 0  + αe − βx ). Lithogenic Fe was used as an indicator, and it revealed the continuous input and accumulation of these four elements in the surrounding soils. Our approach was effective in clearly identifying the sources of metals and analyzing their contamination characteristics. We believe this study will provide useful information to future studies on soil pollution by metals around smelters. Graphical abstract: Image 1 Highlights: Several approaches were combined to identify metal(loid) contamination in soil. As, Cd, Cu, Hg, Pb, and Zn in soils were derived from the Zn smelter. As originated from multiple anthropogenic sources as well as from the Zn smelter. Lithogenic Fe can be an indicator for continuous input of anthropogenic metals. Soil contamination can be effectively investigated with our proposed approach.